2012
DOI: 10.1021/jp306979c
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field-Induced Actuation of Poly(vinyl alcohol) Microfibers

Abstract: Poly(vinyl alcohol) (PVA) microfibers were actuated by application of a direct current (dc) electric field; there were large electrosensitivity differences between water-soluble and high-tenacity fibers. In particular, a bending actuation was observed for water-soluble PVA fibers with high sensitivity and large deformation upon applying a dc electric field. The mechanism of bending actuation was investigated through analysis of the chemical constituents, dielectric properties, bending rigidity, and morphology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The actuation mechanism of PVA microfibers has been partly reported in previous papers . We developed water‐soluble PVA microfibers of diameter 18 μm (2.2 dtex) and with a dissolution temperature in water of 20 °C; we showed that the fibers have excellent actuation ability (bending by 1 mm to the cathode in just 0.4 s).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…The actuation mechanism of PVA microfibers has been partly reported in previous papers . We developed water‐soluble PVA microfibers of diameter 18 μm (2.2 dtex) and with a dissolution temperature in water of 20 °C; we showed that the fibers have excellent actuation ability (bending by 1 mm to the cathode in just 0.4 s).…”
mentioning
confidence: 67%
“…In previous work, we found that some synthetic polymer fibers have electroactive characteristics. The fibers were actuated and showed different behaviors under applied electric stimulation . In particular, polyvinyl alcohol (PVA) microfibers were bent in one direction (to the cathode side) by certain direct current (dc) voltages, with high electrosensitivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The response of a parallel circuit of resistance R and constant phase element (CPE) corresponding to an imperfect capacitor is a semicircle centered below the Z ′‐axis. R is determined from the diameter of the semicircle, and C is calculated from the maximum frequency of the semicircle . As shown in Figure (c–e), the diameters of the semicircles correspond to the interfacial resistances of the film and electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…The strong hydrophilic feature is quite related to the abundance of -OH in the PVA chains and also the highly porous structure. [44] Figure 2. Characterization of the bilayered porous PVA/PS film.…”
Section: Characterization Of the Bilayered Actuatormentioning
confidence: 99%